Human GTPBP5 is involved in the late stage of mitoribosome large subunit assembly. Issue 1 (7th December 2020) - Cipullo, Miriam; Pearce, Sarah F; Lopez Sanchez, Isabel G; Gopalakrishna, Shreekara; Krüger, Annika; Schober, Florian; Busch, Jakob D; Li, Xinping; Wredenberg, Anna; Atanassov, Ilian; Rorbach, Joanna
Abstract: Human mitoribosomes are macromolecular complexes essential for translation of 11 mitochondrial mRNAs. The large and the small mitoribosomal subunits undergo a multistep maturation process that requires the involvement of several factors. Among these factors, GTP-binding proteins (GTPBPs) play an important role as GTP hydrolysis can provide energy throughout the assembly stages. In bacteria, many GTPBPs are needed for the maturation of ribosome subunits and, of particular interest for this study, ObgE has been shown to assist in the 50S subunit assembly. Here, we characterize the role of a related human Obg-family member, GTPBP5. We show that GTPBP5 interacts specifically with the large mitoribosomal subunit (mt-LSU) proteins and several late-stage mitoribosome assembly factors, including MTERF4:NSUN4 complex, MRM2 methyltransferase, MALSU1 and MTG1. Interestingly, we find that interaction of GTPBP5 with the mt-LSU is compromised in the presence of a non-hydrolysable analogue of GTP, implying a different mechanism of action of this protein in contrast to that of other Obg-family GTPBPs. GTPBP5 ablation leads to severe impairment in the oxidative phosphorylation system, concurrent with a decrease in mitochondrial translation and reduced monosome formation. Overall, our data indicate an important role of GTPBP5 in mitochondrial function and suggest its involvement in the late-stage of mt-LSU maturation.